The competitive intelligence process as strategic tool to soccer club - Jorge, Carlos Francisco Bitencourt [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2018)
The information is an intrinsic component of every process in an organization. In the football club environment, it is possible to observe a great competitiveness, and this can be enhanced by means of an efficient management of information, using the process of competitive intelligence. At this bias, this research used to analyze and understand the use of information in the Marília Athletic Club, Football Club of the City of Marília, in the interior of the state of São Paulo. For that, the ‘Case Study’ method was chosen, whose technique is triangulation. With the application of different techniques in an investigative research it makes the same more consistent, thus granting a greater validity to the data and analyzes carried out. These analyzes were carried out with the purpose of elaborating guidelines for the competitive intelligence process for Marília Athletic Club. With the result of the research it was possible to identify the most important types of information of the external environment (sources and information flows) as well as to identify that they are not structured. The research pointed to the lack of information structure in the club, which makes it impossible to practice the competitive intelligence process, thus, it was proposed initial guidelines for the implementation of the process and a better use of the information inserted in the organization.
El proceso de inteligencia competitiva como herramienta estratégica para los clubes de fútbol
O processo de inteligência competitiva como ferramenta estratégica para os clubes de futebol
Keywords: Competitive intelligence; Football clubs; Marília athletic club; Sport environment; Sport information